2023
DOI: 10.1039/d2qi02461f
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-controlled synthesis of an Al12-oxo molecular ring and Al24-oxo truncated metallo-cube

Abstract: Highly symmetrical molecules with beautiful geometry are ubiquitous in nature. It has inspired a creative idea of the perfect combination of geometry and molecular structural chemistry. Some metal clusters with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…[16][17][18] These macrocyclic molecules exhibit distinct benefits in the optics, magnetism and host-guest chemistry domains. [19][20][21][22][23] Yang et al reported a {Nd 18 } molecular ring exhibiting NIR luminescence sensing of antibiotics. 24 Zheng et al synthesized the {Cr 8 Dy 8 } wheel, which is a single-molecule magnet.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] These macrocyclic molecules exhibit distinct benefits in the optics, magnetism and host-guest chemistry domains. [19][20][21][22][23] Yang et al reported a {Nd 18 } molecular ring exhibiting NIR luminescence sensing of antibiotics. 24 Zheng et al synthesized the {Cr 8 Dy 8 } wheel, which is a single-molecule magnet.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33][34] Nevertheless, the development of their luminescence property of Al clusters is still in infancy on account of easy hydrolysis of Al 3+ ion and crystallization difficulty. [30,31,35] Only Fang et al reported a series of Al 20 rings and realize luminescent color tunability from blue, and cyan to green via accommodating the conjugated organic shell on the surface of the clusters. [10] Except for changing the organic shell for Al clusters, the exploration of other methods of tuning luminescent color is of important research significance.…”
Section: Introductionmentioning
confidence: 99%
“…[ 29 ] Recently, Al clusters have become ablaze with a research upsurge due to their light weight and good stability from the strong Al─O bonds. [ 30–34 ] Nevertheless, the development of their luminescence property of Al clusters is still in infancy on account of easy hydrolysis of Al 3+ ion and crystallization difficulty. [ 30,31,35 ] Only Fang et al.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, substantial theoretical and experimental endeavors have been focused on the chemistry of metal–organic frameworks (MOF) due to their captivating structural multiformities and excellent properties. And, metal–organic frameworks based on lanthanide-transition (4f–3d) ions exhibit extraordinary physical as well as chemical properties, particularly in magnetism and photoluminescence. As a result, a large amount of MOFs based on 4f–3d ions have been further explored, for instance, [Ln–Cu], [Ln–Cr], [Ln–Co], [Ln–Ni], and [Ln–Mn]. , In comparison with the well-developed cluster chemistry of metal–organic frameworks based on 4f–3d ions, the chemistry of MOFs based on 4f–3p ions has not been fully explored so far. Aluminum is the most adequate metal in the earth’s crust and is extensively employed in printing fabric, water treatment, catalysis, and optics. It is reported that aluminum also possesses the ability of high luminescence efficiency, making it a suitable material for plasma antennas . The investigation of the mechanism in the improvement of luminescence efficiency by Al III ions has never ceased .…”
Section: Introductionmentioning
confidence: 99%